Penerapan Model CTL Dalam Mengelola Softskill Pada Mata Pelajaran Seni Budaya - Nur 'Azah (Jayapangus Press, 2023)
The focus of this research is to find out the application of the CTL model in the arts and culture subject to manage the soft skills of students at MTsN 1 Jombang which has the goal of becoming an inspiring batik madrasa. The purpose of this study is to describe the implementation of the CTL model in the arts and culture subject and explain the inhibiting and supporting factors for the application of the CTL model. The research method uses a qualitative approach with the type of case study. Sources of data are Arts and Culture teachers, Head of Madrasah and others. Collecting data using interviews and observation. Data analysis using triangulation. The results showed that the application of the CTL model in arts and culture subjects followed the steps of the CTL model (constructivism, inquiry, questioning, learning community, modeling, reflection, authentic assessment) and the inhibiting factors obtained were the obstacles, namely the lack of human resources and natural resources, motivation lacking, differences in enthusiasm between students, inadequate infrastructure, insufficient funds, less time allocation. The supporting factors are support from madrasa organizations, collaboration between art and culture teachers and calligraphy, good responses from batik craftsmen, good responses from various parties, students are more active and focus on learning with group friends, providing insight into job opportunities and training skills. the spirit of entrepreneurship and learning is more colorful and varied. The conclusion is that the application of the CTL model is able to manage students' soft skills well in arts and culture subjects at MTsN 1 Jombang.